How many cell types form the epithelial lining of the human uterine tubes? Revision of the histological nomenclature of the human tubal epithelium - Varga, Ivan; Miko, Michal; Kachlík, David; Žišková, Marianna; Danihel, Ľudovít; Babál, Pavel (Annals of anatomy, 2019)
INTRODUCTION: Many widely used international histological textbooks claim that the epithelium of the human uterine tube consists of two, three, and, eventually, four types of cells. Most discrepancies among these textbooks relate to debates regarding the presence or absence of basal cells, whether the peg/intercalary cells and secretory cells are the same or distinct cell populations, and if the epithelium contains a population of immunologically active cells (T- and B-lymphocytes, NK cells, macrophages and dendritic cells) or dispersed endocrine cells. METHODS: Uterine tubes were obtained from 22 women (average age: 46.73 y) undergoing gynecological surgery. The women were in fertile age, mostly in the middle of the menstrual cycle (ovulation phase). Tissue samples were processed for immunohistochemistry using primary antibodies against proliferation markers (Ki67 and PCNA), immune system cells (CD1a, CD3, CD4, CD8, CD20, CD45RO, CD56, CD68, granzyme B and S100) and disperse endocrine cells (chromogranin A and synaptophysin). RESULTS: Most of the mature tubal epithelial cells, ciliated cells, and secretory cells were mitotically active (PCNA+), a population of basal undifferentiated cells was not identified. The dividing cells had a narrow-shaped nucleus (Ki67 positive). These cells were morphologically identical to - by the terminology mentioned - intercalary cells, assuming they represented actually dividing cells (epitheliocytus tubarius mitoticus). The tubal "basal cells" displayed small, hyperchromatic nuclei and very pale cytoplasm (clear cytoplasmic halo). They were located in the epithelium adjacent to the basement membrane, were non-mitotically active and their immunophenotype corresponded to intraepithelial regulatory T-lymphocytes (CD3+, CD8+, CD45RO+, CD4-, CD20-, CD56- and granzyme B-). Intraepithelial B-lymphocytes were only rarely identified. Intraepithelial NK cells, dendritic cells, macrophages and dispersed endocrine cells were not identified. CONCLUSIONS: We recommend replacing the term "epitheliocytus tubarius basalis" in the Terminologia Histologica with the term "lymphocytus T intraepithelialis tubarius", which represents intraepithelial regulatory T-cells (CD8+, CD45RO+) of the uterine tube. Additionally, we propose that intercalary/peg cells are actively dividing cells, instead of effete or degenerating cells. Finally, the histological nomenclature should be corrected in a way that peg/intercalary cells are not considered synonymous terms for secretory cells.
Keywords: antigen Ki-67; proliferační antigen buněčného jádra; Uterine tube; epitelové buňky; Epithelium; Cell Proliferation; Basal cells; Antigens, CD; Epithelial Cells; CD antigeny; Mitosis; Adult; dospělí; imunohistochemie; Intraepithelial regulatory T-lymphocytes; lidé; ženské pohlaví; Immunohistochemistry; Ki-67 Antigen; Dividing cells; Humans; Fallopian Tubes; vejcovody; proliferace buněk; mitóza; Female; Proliferating Cell Nuclear Antigen; lidé středního věku; Intercalary/peg cells; Middle Aged